Evaluation of the use of reserve antimicrobials by patients hospitalized in establishments of health - Rumiche B., Jesus V. (2008)
It is a of drugs utilization, descriptive, transversal, observational, multicentric study that follows a transversal design, prescription type -indication- with the aim to determine the prevalence use of reserve antimicrobials in hospitalized patients, of all age groups, men and women in services of internal medicine. We applied two sheets of data collection: ATMR-S (for services) and ATMR-P (for patients) to obtain prevalence of reserve antimicrobials (ATMR) and the ATMR prescribed. The sheets were implemented on August 21, 2006 to 845 patients thatwerc hospitalized that day. Wereport an overall prevalence of ATMR prescribing by hospitals is 28%, with extreme values rangingfrom 18% to 38%; theprevalence of use by services is 32.3% with values ranging from 16.4% in obstetrics-gynecology, and 57.1 % in the intensive care unit. ATMR are the most prescribed according to hospital are vancomycin 500 mg. Injection and ceftazidime 1g. with 41.7% in the Guillermo Almenara Hospital and Dos de Mayo respectively; in the Naval Medical Center, 50% of patients of the medicine service was treated with ciprofloxacin 500 mg. Slotted tablet; in the Hospital of the National Police it was prescribed ceftriazone 1g. injection and vancomycin 500 mg.injection by 36%, and 100% of patients treated with ceftriozona 1g. injection. In general, these values are significantly lowerw with ATM in general (60%), but would have to continue monitoring to determine the impact of their use.